Accompanying Students in Online Learning: Challenges and Interventions - Gilbert Santos Arrieta; Reuben C. Calabio; Elna M. Rogel (Universitas Lampung, 2020)
When children come to school, parents endorse them to the teachers and staff who have the duty to take care of their formation and growth while they are in school. Being in school does not only allow the students to learn formally but also to meet new people who become their classmates and friends. The home and school which are the primary places of children/students should be nurturing environments where they grow and assisted. In school, the systems are already in place in terms of teaching and learning including the emotional assistance to students. However, this remains to be seen in a virtual learning environment. The Covid-19 pandemic forced teaching and learning to be conducted in an online environment, a road less traveled in education. Though the learning continuity plan was developed and directives were issued, it was expected that there will be challenges and concerns that will emerge. Managing the challenges experienced by the students is another concern. This study aims to find out the difficulties and challenges encountered by the students as shared and observed by the teachers, and how the students were assisted by the teachers. Based on the findings, it was found out that overload of requirements, time management, isolation, and lack of privacy are the main challenges and concerns encountered by the teachers. According to the teachers and guidance counselors, these were managed by being available online to the students, coordination of the student affairs, teachers, and guidance counselors, listening, and counseling/giving of advice. From these findings, the challenges and concerns will be addressed appropriately and lesser concerns will emerge as the online learning progresses.Keywords: conflicts, learners, online learning, students’ difficulties in virtual learning, managing students in online learning DOI: http://dx.doi.org/10.23960/jiip.v2i2.21787